Inclusion of Intercultural Competence in Integrated Islamic Curriculum for MTs Students in the Post-Pandemic - Krisna Sujaya (UIN Sultan Aji Muhammad Idris Samarinda, 2022)
The purpose of this study was to determine teacher perceptions in the application of an integrated Islamic curriculum based on post-pandemic intercultural competence in the city of Padang. This type of research is a qualitative research with a descriptive approach. Data were collected through observation, interviews, and documentation. Techniques for ensuring the validity of the data were carried out through extension of participation, persistence of observation, triangulation, and peer-checking through discussion. Data analysis techniques are carried out through conducting data reduction, data presentation, and drawing conclusions. The findings show that Islamic religious education teachers explain the subject matter by giving equal attention without discriminating even though students have language, culture, race, and ethnicity. This is in line with the application of the Islamic religious education curriculum in fostering learning to live in diversity in the various Primary School (SD)/Madrasah Ibtidaiyah (MI) Padang City. Cooperative learning is another method used to teach students how to collaborate with one another and respect one another's point of view. Primary School (SD)/Madrasah Ibtidaiyah (MI) in Padang City, the implementation of Islamic religious education curriculum for mutual respect has developed well. Mutual respect is shown by giving everyone the opportunity to practice their religion according to their respective beliefs without demeaning each other but by encouraging each other, congratulating each other, shaking hands, and sincerely apologizing to each other while celebrating religion. Despite the differences that teachers and students may have, The implementation of the Islamic religious education curriculum in fostering open-mindedness has been well established. open-mindedness to refrain from criticizing, making fun of, or demeaning non-Muslim teachers and students.